2018
DOI: 10.1039/c8fo00910d
|View full text |Cite
|
Sign up to set email alerts
|

In vitrodigestion profile and calcium absorption studies of a sea cucumber ovum derived heptapeptide–calcium complex

Abstract: In this study, a novel calcium-binding heptapeptide (NDEELNK) that is released during the trypsin hydrolysis of sea cucumber ovum was identified by peptidomics. The calcium binding mode, in vitro digestion profile and calcium absorption of the NDEELNK-calcium complex were investigated. The NDEELNK peptide could spontaneously bind calcium with a 1 : 1 stoichiometry, and the calcium-binding site might involve the carboxyl oxygen and amino nitrogen atoms of two glutamic acid and one aspartic acid residues in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…The distribution of free Ca 2+ in SCBW was monitored by Fluo‐3 AM and CLSM (Figure ). The fluorescent probe Fluo‐3 AM can bind free Ca 2+ and then emits green fluorescence at emission wavelength from 510 to 525 nm (Cui et al, ). Our results showed that the fluorescence intensity from free Ca 2+ in blank solution treated SCBW increased first and reached a maximum value at 4 hr following the treatment, but decreased thereafter (Figure A–D,I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of free Ca 2+ in SCBW was monitored by Fluo‐3 AM and CLSM (Figure ). The fluorescent probe Fluo‐3 AM can bind free Ca 2+ and then emits green fluorescence at emission wavelength from 510 to 525 nm (Cui et al, ). Our results showed that the fluorescence intensity from free Ca 2+ in blank solution treated SCBW increased first and reached a maximum value at 4 hr following the treatment, but decreased thereafter (Figure A–D,I).…”
Section: Resultsmentioning
confidence: 99%
“…The level of free Ca 2+ in SCBW was visualized in situ using CLSM. This probe, fluo‐3 a.m., was shown to be highly sensitive fluorescence probe for free Ca 2+ (Cui et al, ). The 6‐μm‐thick transverse sections of SCBW were cut by a cryostat microtome and incubated in 100 μM of fluorescent calcium indicator dyes (Fluo‐3 a.m.) for 30 min at 24 ± 1°C.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the excessive cost of AAs, peptides derived from edible seed proteins commonly produced in vivo or in vitro by enzymatic proteolysis are promising ligands for complexation with divalent metals towards improving mineral bioavailability and for alleviating micronutrient deficiency [130,133,134]. To date, a variety of metal-chelating peptides have been generated and identified from different edible seed proteins [135,136]. For instance, Wang et al [137] reported that a pentapeptide FVDVT from wheat germ protein hydrolysate (WGPH) possessed significantly (86%) higher calcium-binding property when compared to crude hydrolysates.…”
Section: Mineral-binding Peptidesmentioning
confidence: 99%
“…As shown in Table 2 , the markers of calcium, iron, and zinc bioavailability were improved when preformed peptide–mineral complexes were used. For instance, calcium absorption was significantly increased in Caco-2 when complexed with NDEELNK and sea cucumber ovum hydrolysate [ 21 ]. Caetano-Silva et al [ 77 ] also observed ferritin synthesis, resulting in a 70% increase in iron uptake when Caco-2 cells were treated with iron complexes with low-molecular weight (<5 kDa) peptides.…”
Section: Solubility Bioavailability and Absorption Of Peptide–minmentioning
confidence: 99%
“…The mineral-chelating properties of peptides are attributed to the structural diversity of their backbone, which contains both the terminal carboxyl and amino groups, and the side chains of amino acid residues [ 5 , 9 ]. To date, a variety of metal-chelating peptides has been generated and identified from different food sources, such as milk, egg, soybean and sea cucumber [ 21 , 22 , 23 , 24 ]. Regardless, caseinophosphopeptides (CPPs) are the most extensively studied mineral-chelating peptides that have been successfully applied as food ingredients for mitigating mineral deficiency [ 20 ].…”
Section: Introductionmentioning
confidence: 99%